Limited matching of the cardiac output response to the peripheral demand of heat stress and exercise - Moritz Lampkemeyer; Jonas Kell; Veit Börß; Tobias Claussen; Fabian Spahiu; Michelle Ottlik; Lars C. Helbig; Craig G. Crandall; Eric J. Stöhr (Experimental Physiology)
Abstract It is widely accepted that cardiac output matches the prevailing peripheral demand in healthy humans. However, it remains unknown whether stroke volume and heart rate are regulated interdependently to arrive at a specific cardiac output. The aim of this study was to determine whether the healthy human heart responds specifically according to the peripheral demands of heat stress and exercise. Eleven healthy humans (women/men n = 3/8; age = 26 ± 2 years; body mass = 73 ± 11 kg) underwent leg heat stress and cycling exercise (60 W), with and without blood flow restriction (pressure set at the prevailing mean arterial pressure of the individual). Cardiac output was measured with triplane echocardiography. Additionally, haemodynamics, oxygen consumption, carbon dioxide production and lactate were assessed. Data were analysed using two‐way repeated‐measures ANOVA. Despite stable heat and exercise demands, cardiac output decreased significantly with blood flow restriction in both conditions (Δ−0.87 and −1.03 L min−1, 17% and 11%, respectively, p = 0.01), owing to a decline in end‐diastolic volume (p < 0.0001) and stroke volume (p < 0.0001) not sufficiently compensated for by an increase in heart rate (p = 0.001). Importantly, these responses were accompanied by an increased rate of skin temperature rise (p = 0.04) during heat stress and a significantly greater rise in circulating lactate (p < 0.0001) during exercise. The cardiac output response to local heat stress and submaximal exercise does not appear to be entirely specific to the peripheral thermal and energetic requirements. This finding supports the theory that even the healthy heart does not coordinate stroke volume and heart rate to arrive at a specific target output.